2002
DOI: 10.1901/jeab.2002.77-91
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discrimination Under Concurrent Variable‐ratio Variable‐ratio Schedules

Abstract: Pigeons were trained to discriminate 5 mg/kg pentobarbital from saline under concurrent variable-ratio (VR) VR schedules, in which responses on the pentobarbital-biased lever were reinforced under the VR schedule with the smaller response requirements when pentobarbital was given before the session, and responses on the saline-biased key were reinforced under the VR schedule with the larger response requirements. When saline was administered before the session, the reinforcement contingencies associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The extent to which this is a fundamental characteristic of behavior under the control of drug discriminative stimuli or an outcome of the particular training parameters remains unclear. The few drug discrimination studies that have used variable-ratio schedules have produced relatively graded dose–response functions in individual subjects (Holloway & Gauvin, 1989; McMillan, Hardwick, & Li, 2002). Determining the conditions under which drug discrimination and generalization is quantal or graded would provide fundamental information regarding private responses to drug stimuli.…”
Section: Future Directionsmentioning
confidence: 99%
“…The extent to which this is a fundamental characteristic of behavior under the control of drug discriminative stimuli or an outcome of the particular training parameters remains unclear. The few drug discrimination studies that have used variable-ratio schedules have produced relatively graded dose–response functions in individual subjects (Holloway & Gauvin, 1989; McMillan, Hardwick, & Li, 2002). Determining the conditions under which drug discrimination and generalization is quantal or graded would provide fundamental information regarding private responses to drug stimuli.…”
Section: Future Directionsmentioning
confidence: 99%
“…That is, behavior is allocated between concurrently available sources of reinforcement so as to match the relative rates of reinforcement obtained from those alternatives. In addition, it has been shown that preference exists for variable over fixed schedules or reinforcement (Ahearn, Hineline, & David, 1992; Field, Tonneaau, Ahearn, & Hineline, 1996), and for the smaller ratio in concurrent variable-ratio (VR) schedules (Hernstein and Loveland, 1975; MacDonall, 1988; McMillan, Hardwick & Li, 2002).…”
mentioning
confidence: 99%